IgG4-Related Orbital Disease: An Analysis of Patient Profiles, Clinical Presentation, And Histopathological Features - Fariha Taimur; Amna Manzoor; Muhammad Saad; Faizan Tahir; Sumeya Khan; Aashar Khalid (Journal of Rawalpindi Medical College)
Objective: To study various presentations of patients with a histopathologically confirmed diagnosis of IgG4 disease.